Hanne Veber, Jens Dahl, Fiona Wilson & Esben Wæhle (eds): "...NEVER DRINK FROM THE SAME CUP": Proceedings of the Conference on Indigenous Peoples in Africa - Kanyinga, Karuti (Tidsskriftet Antropologi, 2019)
Hanne Veber, Jens Dahl, Fiona Wilson & Esben Wæhle (eds): "...NEVER DRINK FROM THE SAME CUP": Proceedings of the Conference on Indigenous Peoples in Africa Anmeldes af Karuti Kanyinga